2014
DOI: 10.1007/s00500-014-1322-9
|View full text |Cite
|
Sign up to set email alerts
|

Random-key cuckoo search for the travelling salesman problem

Abstract: Combinatorial optimization problems are typically NP-hard, and thus very challenging to solve. In this paper, we present the random key cuckoo search (RKCS) algorithm for solving the famous Travelling Salesman Problem (TSP). We used a simplified random-key encoding scheme to pass from a continuous space (real numbers) to a combinatorial space. We also consider the displacement of a solution in both spaces using Lévy flights. The performance of the proposed RKCS is tested against a set of benchmarks of symmetri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 27 publications
0
33
0
Order By: Relevance
“…However, the salesman using this approach may be stuck at local minima because this approach does not effectively address the diversity of feasible solutions. Recently, two new approaches are proposed by Ouaarab et al (2015), and Yong (2015). Ouaarab et al (2015) used a simplified random-key encoding scheme to pass from a continuous space (real numbers) to a combinatorial space.…”
Section: Literature Review 21 Traveling Salesman Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the salesman using this approach may be stuck at local minima because this approach does not effectively address the diversity of feasible solutions. Recently, two new approaches are proposed by Ouaarab et al (2015), and Yong (2015). Ouaarab et al (2015) used a simplified random-key encoding scheme to pass from a continuous space (real numbers) to a combinatorial space.…”
Section: Literature Review 21 Traveling Salesman Problemmentioning
confidence: 99%
“…Recently, two new approaches are proposed by Ouaarab et al (2015), and Yong (2015). Ouaarab et al (2015) used a simplified random-key encoding scheme to pass from a continuous space (real numbers) to a combinatorial space. They also considered the displacement of a solution in both spaces using Lévy flights.…”
Section: Literature Review 21 Traveling Salesman Problemmentioning
confidence: 99%
“…In fact, it is observed in the simulations that CS is indeed scale-free and have a fractal-like search structure. Consequently, CS can be very effective for nonlinear optimization problems and multiobjective optimization [17,36,30,58,64].…”
Section: Algorithms Based On Swarm Intelligencementioning
confidence: 99%
“…For VMS and VMP, a new algorithm called VM selection and placement using Random Key Cuckoo search (VMSPRKCS), was proposed to handle both VMS and VMP steps. Random Key Cuckoo Search (RKCS) [10] is a novel approach using Cuckoo Search (CS) [11], based on random keys encoding schema (RKES) [12]. CloudSim [13], with a real data set presented from PlanetLab [14], has been used to evaluate the proposed algorithm, and the experimental results showed that the proposed algorithm significantly reduces the consumed energy as well as SLAV.…”
Section: Introductionmentioning
confidence: 99%